CRISPR-Cas9 and CRISPR-Cpf1 mediated targeting of a stomatal developmental gene EPFL9 in rice - Zhang, Shilai; Hu, Jian; Yang, Chundao; Liu, Haitao; Yang, Feng; Zhou, Jihua; Samson, Ben K.; Boualaphanh, Chanthakhone; Huang, Liyu; Huang, Guangfu; Zhang, Jing; Huang, Wanqi; et al. (Elsevier, 2017)
The introduction and utilization of systems biology approaches have identified several genes that are involved in early development of a plant and with such knowledge a robust tool is required for the functional validation of putative candidate genes thus obtained. The development of the CRISPR-Cas9/Cpf1 genome editing system has provided a convenient tool for creating loss of function mutants for genes of interest. The present study utilized CRISPR/Cas9 and CRISPR-Cpf1 technology to knock out an early developmental gene EPFL9(Epidermal Patterning Factor like-9, a positive regulator of stomatal development inArabidopsis) orthologue in rice. Germ-line mutants that were generated showed edits that were carried forward into the T2 generation when Cas9-free homozygous mutants were obtained. The homozygous mutant plants showed more than an eightfold reduction in stomatal density on the abaxial leaf surface of the edited rice plants. Potential off-target analysis showed no significant off-target effects. This study also utilized the CRISPR-LbCpf1 (Lachnospiracaebacterium Cpf1) to target the same OsEPFL9 gene to test the activity of this class-2 CRISPR system in rice and found that Cpf1 is also capable of genome editing and edits get transmitted through generations with similar phenotypic changes seen with CRISPR-Cas9. This study demonstrates the application of CRISPR-Cas9/Cpf1 to precisely target genomic locations and develop transgene-free homozygous heritable gene edits and confirms that the loss of function analysis of the candidate genes emerging from different systems biology based approaches, could be performed, and therefore, this system adds value in the validation of gene function studies